Vulcanized nano zero-valent iron, preparation method thereof and method for removing thallium from wastewater

By preparing vulcanized nano zero-valent iron (S0@nZVI) as a thallium removal material, the problems of high cost of thallium treatment and unstable treatment effect in water bodies in the prior art are solved, and efficient and environmentally friendly wastewater thallium removal effect is achieved.

CN119588298APending Publication Date: 2025-03-11HUNAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411579853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-11

Smart Images

  • Figure CN119588298A_ABST
    Figure CN119588298A_ABST
Patent Text Reader

Abstract

The invention provides vulcanized nano zero-valent iron, a preparation method of the vulcanized nano zero-valent iron and a method for removing thallium from wastewater. The preparation method of the vulcanized nano zero-valent iron comprises the following steps: adding nano zero-valent iron into oxygen-free deionized water, and carrying out first stirring treatment to obtain a nano zero-valent iron suspension; sodium sulfide nonahydrate is added into the nanometer zero-valent iron suspension liquid for second stirring treatment, and a sulfur-containing solution is obtained; ferric trichloride hexahydrate is added into the sulfur-containing solution for third stirring treatment, and a vulcanized product is obtained; and carrying out solid-liquid separation on the vulcanized product to obtain the vulcanized nano zero-valent iron. The vulcanized nano zero-valent iron prepared by the method has unique active sites and excellent adsorption capacity, and can effectively capture thallium in an ionic state in a water body. In addition, the vulcanized nano zero-valent iron prepared by the method is applied to wastewater thallium removal treatment, can be separated by a magnetic separation method, cannot cause secondary pollution to a water body environment, and has relatively good sustainability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thallium removal from wastewater, and in particular relates to sulfided nanometer zero-valent iron, a preparation method of sulfided nanometer zero-valent iron and a method for removing thallium from wastewater. Background Art

[0002] Thallium (Tl) is a highly toxic trace heavy metal element, which is far more toxic than copper, lead, zinc and cadmium, and even more toxic than arsenic and methylmercury. Thallium is present in very low levels in the natural environment, but it has the characteristics of being philic and sulfur-loving. It is widely distributed in various ores and minerals, and is easily enriched in low-temperature thallium, lead, zinc, antimony, mercury, arsenic and other deposits, Carlin-type gold deposits, sedimentary manganese ores, salt mines and polymetallic deposits. Thallium-containing rocks and deposits release a large amount of thallium into the environment under leaching and secondary oxidation. Thallium is easily soluble in water, especially in mine wastewater and smelting wastewater, where it is highly concentrated.

[0003] At present, the commonly used methods for treating thallium-containing wastewater in my country include oxidation, precipitation, adsorption, ion exchange, biological method, membrane method, etc. The precipitation method mainly uses fluorine and other ions to form insoluble substances to remove them from water, thereby achieving the purpose of removing thallium. In order to achieve a better thallium removal effect, a large amount of precipitants, such as lime or aluminum salts, may be required, which not only increases the cost, but also may cause the problem of residual reagents. The adsorption method mainly uses specific materials to selectively remove thallium from thallium-containing wastewater, thereby achieving the purpose of removing thallium. The adsorption method is a widely applicable thallium-containing wastewater treatment technology, and its key lies in the preparation of thallium removal materials. The oxidation method has a significant pretreatment effect, but the dosage of the reagent is large, the cost is high, and it is easy to cause secondary pollution. The precipitation method is widely used, but its treatment depth is limited and there is a risk of secondary pollution. The adsorption method does not require the addition of chemical auxiliary reagents, has low cost and is easy to operate, but is greatly affected by coexisting ions and consumes a lot of adsorbents. The ion exchange method is simple to operate and has little secondary pollution, but the resin exchange capacity is easily disturbed and needs frequent regeneration, and the treatment effect is limited. The biological method can be applied to the treatment of thallium-containing acidic wastewater, but the growth conditions, tolerance and impact resistance of microorganisms are still limited. Although the membrane method has the characteristics of energy saving, no phase change and easy operation, the effect is unstable, the membrane is easy to clog, and the maintenance cost is high. In general, the existing technology for treating thallium in water still needs to be improved. Summary of the invention

[0004] Therefore, in order to overcome at least some of the defects and shortcomings in the prior art, the embodiments of the present invention provide a sulfide nano zero-valent iron, a method for preparing sulfide nano zero-valent iron, and a method for removing thallium from wastewater. The sulfide nano zero-valent iron prepared by the present invention has a high adsorption capacity, can effectively capture ionic thallium in water, and has a high thallium removal efficiency.

[0005] On the one hand, an embodiment of the present invention provides a method for preparing sulfide nano zero-valent iron, comprising: adding nano zero-valent iron to oxygen-free deionized water for a first stirring treatment to obtain a nano zero-valent iron suspension; adding sodium sulfide nonahydrate to the nano zero-valent iron suspension for a second stirring treatment to obtain a sulfur-containing solution; adding ferric chloride hexahydrate to the sulfur-containing solution for a third stirring treatment to obtain a sulfide product; and performing solid-liquid separation on the sulfide product to obtain sulfide nano zero-valent iron.

[0006] In one embodiment of the present invention, the molar ratio of the sodium sulfide nonahydrate to the nano zero-valent iron is 0.06:1 to 0.24:1; and / or the molar ratio of the ferric chloride hexahydrate to the sodium sulfide nonahydrate is 2:1.

[0007] In one embodiment of the present invention, the nano zero-valent iron is prepared by any one of the following preparation methods: liquid phase reduction preparation method, ball milling method, electrolytic preparation method, and green synthesis preparation method.

[0008] In one embodiment of the present invention, the first stirring treatment is carried out under a protective gas atmosphere, the stirring speed of the first stirring treatment is 50 to 200 rpm, and the stirring time of the first stirring treatment is 10 to 30 min; and / or, the second stirring treatment is carried out under a protective gas atmosphere, the stirring speed of the second stirring treatment is 50 to 200 rpm, and the stirring time of the second stirring treatment is 10 to 20 min; and / or, the third stirring treatment is carried out under a protective gas atmosphere, the stirring speed of the third stirring treatment is 50 to 200 rpm, and the stirring time of the third stirring treatment is 0.5 to 3.0 h.

[0009] In one embodiment of the present invention, after the sulfidation product is subjected to solid-liquid separation to obtain sulfided nano zero-valent iron, the method further includes: washing the sulfided nano zero-valent iron with oxygen-free deionized water to obtain washed sulfided nano zero-valent iron; the washing times are 1 to 5 times; freeze-drying the washed sulfided nano zero-valent iron in a vacuum atmosphere to obtain dried sulfided nano zero-valent iron; the freeze-drying time is 8 to 12 hours.

[0010] On the other hand, the present invention provides a sulfide nanometer zero-valent iron, which is prepared by the above-mentioned preparation method of sulfide nanometer zero-valent iron.

[0011] In one embodiment of the present invention, the chemical formula of the sulfide nano zero-valent iron is S 0 @nZVI.

[0012] In another aspect, the present invention provides a method for removing thallium from wastewater, using the aforementioned sulfide nano zero-valent iron to remove thallium from the thallium-containing wastewater to be treated.

[0013] In one embodiment of the present invention, the method comprises: adding the sulfide nano zero-valent iron to the thallium-containing wastewater to be treated with a pH value of 3 to 11 to remove thallium and obtain a reaction product; the pH value of the thallium-containing wastewater to be treated is in the range of 3 to 11; and performing solid-liquid separation on the reaction product to obtain the thallium-removed liquid and thallium-removed slag.

[0014] In one embodiment of the present invention, based on the volume of the thallium-containing wastewater, the thallium concentration of the thallium-containing wastewater is 5 mg / L, and the dosage of the sulfide nano zero-valent iron is 50-500 mg / L.

[0015] It can be seen from the above that the above technical solution has at least one or more of the following beneficial effects:

[0016] The present invention uses the above-mentioned sulfide nano zero-valent iron preparation method to prepare a sulfide nano zero-valent iron material with high adsorption capacity, which can effectively capture ionic thallium in water and has a high thallium removal efficiency. Secondly, when sulfide nano zero-valent iron is used in the process of wastewater thallium removal, no additional chemical auxiliary reagents are required, the treatment process is simple and economical, and has good environmental adaptability. In addition, when sulfide nano zero-valent iron is used in wastewater thallium removal, its reaction product is mainly Tl x S y with Fe x O y The reaction product has good stability, will not cause secondary pollution to the water environment, and can be separated by magnetic separation, so it has good sustainability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0018] Figure 1 A schematic flow chart of a method for preparing sulfide nano zero-valent iron provided in an embodiment of the present invention.

[0019] Figure 2 for Figure 1 Schematic diagram of the specific steps involved in S1.

[0020] Figure 3 for Figure 1 Schematic diagram of the process of additional steps after step S5.

[0021] Figure 4 A schematic flow chart of a method for removing thallium from wastewater provided in an embodiment of the present invention.

[0022] Figure 5 This is a structural diagram of the sulfide nano zero-valent iron provided in an embodiment of the present invention.

[0023] Figure 6 The morphology of the sulfide nano-zero-valent iron prepared in the specific example is a scanning electron microscope (SEM) image.

[0024] Figure 7 This is the X-ray diffraction pattern (XRD) of the sulfide nano-zero-valent iron prepared in a specific embodiment.

[0025] Figure 8 This is a curve chart showing the change in thallium removal from wastewater with different dosages of sulfide nano-zero-valent iron over time.

[0026] Fig. 9 The figure is a curve showing the effect of sulfide nano-zero-valent iron on removing thallium-containing wastewater under different molar ratios of sodium sulfide nonahydrate to nano-zero-valent iron.

[0027] Fig.10 This is a curve chart showing the effect of the generated sulfide nano-zero-valent iron on removing thallium-containing wastewater under different stirring times of the third stirring treatment.

[0028] Fig.11 The removal rate of thallium-containing wastewater by sulfide nano-zero-valent iron in thallium-containing wastewater with different pH values.

[0029] Fig.12 A bar chart showing the removal rate of thallium-containing wastewater by sulfide nano-zero-valent iron in a simulated industrial wastewater solution containing lead ions, zinc ions, nitrate and sulfate.

[0030] Fig.13 Different sulfide nano zero-valent iron (S 0 @nZVI, S 0 / nZVI、FeS@nZVI、FeS / nZVI、FeSx@nZVI、S 0 comm / nZVI) for the removal rate of thallium-containing wastewater. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work should fall within the scope of protection of the present invention.

[0032] In natural water environment, Tl + and Tl3+ There are two oxidation states of thallium, Tl + It is the dominant species in the water, and Tl + The strong mobility of Tl + The sulfide nano zero-valent iron (S 0 @nZVI) is used to adsorb thallium ions in thallium-containing wastewater.

[0033] like Figure 1 and Figure 5 As shown, the embodiment of the present invention provides a sulfide nanometer zero-valent iron and a method for preparing the sulfide nanometer zero-valent iron. Figure 4 As shown, the sulfide nano zero-valent iron can be used for thallium removal from thallium-containing wastewater. Specifically, the preparation method of sulfide nano zero-valent iron, for example, includes the following steps:

[0034] S2: adding nano zero-valent iron into oxygen-free deionized water for a first stirring treatment to obtain a nano zero-valent iron suspension;

[0035] S3: adding sodium sulfide nonahydrate to the nano zero-valent iron suspension for a second stirring treatment to obtain a sulfur-containing solution;

[0036] S4: adding ferric chloride hexahydrate to the sulfur-containing solution for a third stirring treatment to obtain a sulfurized product;

[0037] S5: performing solid-liquid separation on the sulfided product to obtain sulfided nanometer zero-valent iron.

[0038] Specifically, in step S2, nano zero-valent iron is added to oxygen-free deionized water for a first stirring treatment to form a nano zero-valent iron suspension. The nano zero-valent iron content in the nano zero-valent iron suspension is, for example, 4 g / L, which helps to alleviate the aggregation between particles and improve the dispersibility of nanoparticles before the sulfidation reaction, providing a good foundation for the subsequent sulfidation reaction. In step S3, sodium sulfide nonahydrate (Na 2 S·9H 2 The addition of ferric chloride hexahydrate is to introduce a sulfur source into the nano zero-valent iron suspension to prepare for the sulfurization reaction on the surface of the nano zero-valent iron. The addition of is to strengthen the sulfurization reaction on the surface of nano zero-valent iron. The reaction formula is: S 2- +2Fe 3+ →S 0 +2Fe 2+ , thereby promoting the formation of a sulfide layer on the surface of nano zero-valent iron, so that the sulfur layer can form a uniform coverage on the surface of nano zero-valent iron, constructing the S 0@nZVI has a core-shell structure. This structure optimizes the adsorption performance of the material, provides more active sites, and helps to quickly capture and remove thallium ions in water. Steps S3 to S4 are used to sulfide the nano-zero-valent iron. After sulfide modification, the nano-zero-valent iron has unique surface properties, high adsorption capacity, and strong stability. It can effectively capture ionic thallium in water and has a high thallium removal efficiency. In addition, the sulfur layer increases the S 0 @nZVI's selectivity for specific ions makes S 0 @nZVI can also effectively remove ionic thallium in complex water bodies (such as wastewater containing multiple heavy metal ions). Fig.12 , Fig.12 To simulate the industrial wastewater solution containing lead ions, zinc ions, nitrate and sulfate, sulfide nano zero-valent iron (S 0 @nZVI) The bar graph of the removal rate of thallium-containing wastewater, from Fig.12 It can be seen that S 0 @nZVI can also efficiently remove ionic thallium in complex water bodies (e.g., wastewater containing lead ions, zinc ions, nitrate ions, and sulfate ions). In step S5, the sulfided nano-zero-valent iron is separated from the solution by solid-liquid separation technology, such as centrifugation or filtration, to ensure the purity and stability of the sulfided nano-zero-valent iron and avoid interference from unreacted chemical reagents and other impurities.

[0039] The present invention prepares sulfide nanometer zero-valent iron by S1 to S5. The chemical formula of sulfide nanometer zero-valent iron is S 0 @nZVI, sulfide nano zero-valent iron (S 0 @nZVI) structure diagram Figure 5 As shown, sulfide nano zero-valent iron (S 0 @nZVI) SEM picture Figure 6 As shown, sulfide nano zero-valent iron (S 0 @nZVI) is shown in the attached XRD pattern Figure 7 As shown, from Figure 7 It can be seen that there are two zero-valent iron peaks, no additional structures are generated, and sulfur is in an amorphous state. 0 " represents sulfur, "@" represents core-shell structure, "nZVI" represents nanoscale zero-valent iron, S 0 @nZVI means "S 0 "As a shell wrapping the outside of nano zero-valent iron (nZVI), forming S 0 @nZVI structure. Due to its large specific surface area and special chemical properties, the prepared sulfide nano zero-valent iron has a high adsorption capacity and can effectively capture ionic thallium in water, with a high thallium removal efficiency.

[0040] In the method for preparing sulfide nano zero-valent iron provided in an embodiment of the present invention, the nano zero-valent iron in step S2 can be prepared by, for example, a liquid phase reduction preparation method, a ball milling method, an electrolytic preparation method, or a green synthesis preparation method. Figure 2 The method for preparing sulfide nano zero-valent iron provided by the embodiment of the present invention also includes step S1: preparing the nano zero-valent iron by any one of liquid phase reduction preparation method, ball milling method, electrolysis preparation method and green synthesis preparation method.

[0041] Among them, the liquid phase reduction preparation method is, for example, adding borohydride to reduce trivalent iron to generate zero-valent iron; the ball milling method is, for example, the metal iron powder is run in a high-energy ball mill for a long time to produce nano zero-valent iron powder, and the micron-level or millimeter-level iron powder is ground into nano-level particles in the ball mill by mechanical force; the electrolytic preparation method is, for example, electrolyzing the iron anode in a suitable electrolyte solution to generate nZVI on the cathode for synthesizing nano-level zero-valent iron particles; the green synthesis preparation method is, for example, using the components in plant extracts (such as plant leaves, rhizomes, fruits, etc.) as reducing agents and stabilizers to prepare nZVI, and the biologically active components in these plant extracts can effectively reduce metal ions and provide a stable coating layer on the surface of the formed nZVI particles, or using microorganisms (such as bacteria, fungi, etc.) to reduce metal ions under suitable culture conditions to synthesize nZVI. Of course, the above is only an example, and this embodiment is not limited to this.

[0042] Since nano-sized zero-valent iron provides a larger specific surface area, the number of reactive sites is increased, thereby increasing the reaction rate. Zero-valent iron itself has strong reducing properties and can reduce a variety of heavy metal ions and convert them into insoluble or low-toxic forms. The sulfide layer formed on the surface of nano zero-valent iron by sulfidation treatment increases the adsorption capacity for specific heavy metal ions and improves the removal efficiency. Sulfided nano zero-valent iron has a large contact area with pollutants and a fast reaction rate, and can remove pollutants in a relatively short time. Therefore, sulfided nano zero-valent iron has excellent adsorption capacity and can quickly process heavy metal ions. This unique active site enables it to capture ionic thallium in water in a relatively short time, and the thallium removal efficiency is high.

[0043] Specifically, the molar ratio of the sodium sulfide nonahydrate to the nano zero-valent iron is 0.06:1 to 0.24:1; and / or, the molar ratio of the ferric chloride hexahydrate to the sodium sulfide nonahydrate is 2:1. The present invention ensures that there are enough sulfur ions to react with iron atoms to form a sulfur single layer by setting the molar ratio of the sodium sulfide nonahydrate to the nano zero-valent iron to 0.06:1 to 0.24:1, while avoiding excessive sulfurization leading to a decrease in the thallium removal performance of the material. An appropriate amount of sulfur single layer can also prevent the oxidation of nano zero-valent iron and improve the stability of the material under different environmental conditions. By setting the molar ratio of the sodium sulfide nonahydrate used for sulfurization treatment and the ferric chloride hexahydrate that further promotes sulfurization treatment to 2:1, it can ensure that the sulfur ions and the iron ions react sufficiently to form the required sulfur single layer, which is conducive to forming a uniform sulfur single layer on the surface of the zero-valent iron and preventing excessive sulfurization from causing a decrease in the thallium removal performance of the prepared material.

[0044] Specifically, the present invention optimizes the stirring speed and stirring time of the first stirring treatment of nano zero-valent iron and oxygen-free deionized water to 50-200 rpm (revolutions per minute) and 10-30 min, respectively, thereby ensuring the uniform dispersion of nano zero-valent iron in oxygen-free deionized water, preventing oxidation and aggregation, improving material stability and reaction efficiency, and facilitating large-scale production and application.

[0045] Specifically, the present invention optimizes the stirring speed and stirring time of the second stirring treatment of the sodium sulfide nonahydrate and the nano zero-valent iron suspension to 50-200 rpm and 10-20 min, respectively, thereby ensuring the full reaction of the sodium sulfide nonahydrate and the nano zero-valent iron to form a uniform sulfur-containing solution, thereby promoting the uniform formation of a sulfur single layer.

[0046] Specifically, the present invention optimizes the stirring speed and stirring time of the third stirring treatment of ferric chloride hexahydrate and the sulfur-containing solution to 50-200 rpm and 0.5-3.0 h, respectively, to ensure that ferric chloride hexahydrate and the sulfur-containing solution are fully contacted and reacted to form a uniform sulfide product. This helps to improve the quality of the sulfide layer, enhance the stability and adsorption performance of the material, while avoiding local oversaturation or uneven sulfidation, and ensuring the efficient preparation of sulfided nano zero-valent iron. Among them, reference Fig.10 , Fig.10 The different curves in the figure are the sulfide nano zero-valent iron (S) obtained under different stirring times (0.5h to 3h) of the third stirring treatment. 0 @nZVI) shows the change curve of thallium removal from wastewater (thallium content is 5 mg / L) over time (0-180 min). As time goes by, the smaller the value of thallium post-reaction concentration / pre-reaction concentration is, the better the thallium removal effect is.

[0047] The above-mentioned S10-S40 processes are carried out in a protective gas atmosphere, which is used to effectively avoid oxidation reactions and maintain the stability of the reaction system. For example, the protective gas is argon, and the inertness of argon prevents the oxidation of nano zero-valent iron and ensures that the sulfidation reaction proceeds stably.

[0048] like Figure 3 As shown, a method for preparing sulfided nano zero-valent iron provided by an embodiment of the present invention, after solid-liquid separation of the sulfided product to obtain sulfided nano zero-valent iron, for example, further comprises the following steps:

[0049] S51: washing the sulfide nanometer zero-valent iron with oxygen-free deionized water to obtain washed sulfide nanometer zero-valent iron;

[0050] S52: freeze-drying the washed sulfide nano zero-valent iron in a vacuum atmosphere to obtain dried sulfide nano zero-valent iron.

[0051] In step S51, the sulfide nano-zero-valent iron is washed with oxygen-free deionized water for 1 to 5 times, the purpose of which is to remove reactants, by-products or impurities that may remain in the suspension, such as unreacted sodium sulfide and ferric chloride, or non-target sulfides such as ferrous sulfide, which helps to ensure the purity of the sulfide nano-zero-valent iron.

[0052] In step S52, freeze drying is performed in a vacuum atmosphere to remove moisture from the washed nano-zero-valent iron sulfide, while avoiding possible oxidation or structural changes of the material at high temperatures. Freeze drying retains the pore structure and specific surface area of ​​the material, which helps to maintain the adsorption performance of the material. The freeze drying time is, for example, 8 to 12 hours, and the freeze drying temperature is, for example, -40 to -60°C, to ensure that the moisture in the nano-zero-valent iron sulfide is completely removed, while avoiding possible sample structure damage or excessive shrinkage due to excessive drying time.

[0053] like Figure 4 As shown, the method for removing thallium from wastewater provided by the embodiment of the present invention uses the sulfide nano zero-valent iron prepared by the above preparation method to remove thallium from the thallium-containing wastewater to be treated, and the specific steps include:

[0054] S60: adding the sulfide nano zero-valent iron to the thallium-containing wastewater to be treated to remove thallium, thereby obtaining a reaction product; the pH value of the thallium-containing wastewater to be treated is in the range of 3 to 11;

[0055] S70: performing solid-liquid separation on the reaction product to obtain the thallium-free liquid and thallium-free slag.

[0056] Specifically, in step S60, when the pH value of the thallium-containing wastewater to be treated is between 3 and 11, the removal rate is higher than 99%. Fig.11 , Fig.11 The sulfide nanometer zero-valent iron (S) in thallium-containing wastewater with different pH values 0 @nZVI) removal rate of thallium-containing wastewater, from Fig.11 It can be seen that when the pH value of thallium-containing wastewater is between 3 and 11, the sulfide nano zero-valent iron is added to the thallium-containing wastewater, and the sulfide nano zero-valent iron can effectively react with thallium ions and effectively remove thallium from the wastewater. Since thallium-containing wastewater generally needs to be pretreated in the wastewater treatment process, and the source of thallium-containing wastewater may be different, the pH values ​​of different thallium-containing wastewaters may be different. The sulfide nano zero-valent iron provided by the above embodiment of the present invention can efficiently remove thallium from the thallium-containing wastewater to be treated in the pH range of 3 to 11, and is not limited by the extremely acidic or alkaline conditions of the thallium-containing wastewater. Therefore, for thallium-containing wastewater of various pH values, the sulfide nano zero-valent iron provided in this embodiment can be directly used to remove thallium without adjusting the pH value. And the temperature of the thallium removal reaction can be 15 to 45°C, that is, at normal ambient temperature, a good thallium removal effect can be achieved, without additional heating, and the cost is lower. In step S70, the product obtained by the thallium removal reaction is easy to separate. The product obtained by the thallium removal reaction is subjected to solid-liquid separation to obtain a thallium-removed liquid. The thallium-removed liquid can be directly utilized or discharged if it meets the emission standards after testing. The thallium removal slag, for example, includes hydroxide precipitate formed after sulfide nano-zero-valent iron adsorbs thallium-containing wastewater.

[0057] Among them, the thallium concentration of the thallium-containing wastewater is 5 mg / L based on the volume of the thallium-containing wastewater, and the dosage of the sulfide nano zero-valent iron is 50-500 mg / L. Within this dosage range, it can be ensured that there are enough active sites to interact with thallium ions, thereby achieving efficient thallium removal, which is suitable for various thallium-containing wastewater treatment scenarios, including metal smelting plant wastewater, etc. Figure 8 , Figure 8 The vertical axis is the concentration of thallium in the wastewater after reaction / the concentration before reaction. Figure 8 The horizontal axis is time. Figure 8 The different curves are the curves of the removal of thallium from wastewater (containing thallium of 5 mg / L) by different dosages (50-500 mg / L) of sulfide nano-zero-valent iron over time (0-180 min). Figure 8 It can be seen that as time goes by, the value of thallium concentration after reaction / concentration before reaction becomes smaller, indicating that the amount of thallium removed is higher. Figure 8 It can be seen that when the dosage is 300 mg / L and the thallium removal treatment is carried out for 30 minutes, the ratio of the thallium concentration after the reaction to the concentration before the reaction has dropped to a lower value and no longer changes significantly, indicating that the thallium in the wastewater has been basically removed at this time, and the removal efficiency has reached a high level, and the thallium removal effect is good.

[0058] In other embodiments, by controlling the ratio of the added sodium sulfate nonahydrate and the additional iron source (e.g., ferrous chloride hexahydrate, ferrous sulfate heptahydrate), the sulfur content and morphology of the sulfided nano-zero-valent iron can be precisely controlled, and sulfided nano-zero-valent iron with different sulfur morphologies can be prepared, including but not limited to the following representative morphologies: S 0 / nZVI(Surface Adhesion S 0 )、FeS@nZVI、FeS / nZVI(surface-adhered FeS)、FeSx@nZVI、S 0 comm / nZVI (surface-adhered sulfur element S 0 Commercial , where S 0 Commercial Abbreviation S 0 comm ). Reference Fig.13 , Fig.13 Different sulfide nano zero-valent iron (S 0 @nZVI, S 0 / nZVI、FeS@nZVI、FeS / nZVI、FeSx@nZVI、S 0 comm / nZVI) for the removal rate of thallium-containing wastewater, from Fig.13 It can be seen that S 0 @nZVI has the highest removal rate for thallium-containing wastewater.

[0059] The following are some examples of methods and steps for obtaining the above-mentioned sulfide nano zero-valent iron with different sulfur forms:

[0060] Example 1: (1) Under a protective atmosphere (argon), sodium sulfide nonahydrate is added to oxygen-free deionized water and stirred at a speed of 50 to 200 rpm; (2) Under a protective atmosphere (argon), ferric chloride hexahydrate is fully dissolved in the solution in step (1), stirred for 10 minutes, and stirred at a speed of 50 to 200 rpm, wherein the molar ratio of ferric chloride hexahydrate to sodium sulfide nonahydrate is 2:1; (3) Nano-zero-valent iron is prepared by any one of a liquid phase reduction preparation method, a ball milling method, an electrolytic preparation method, and a green synthesis preparation method, and the mixture is stirred at a speed of 50 to 200 rpm. Under a protective atmosphere, the nanometer zero-valent iron is added to the solution in step (2) at a stirring speed of 50 to 200 rpm, wherein the molar ratio of sodium sulfide nonahydrate to the nanometer zero-valent iron is 0.24:1 to 0.06:1; (4) the solution in step (3) is further stirred to obtain black particles at a stirring speed of 50 to 200 rpm for a stirring time of 0.5 to 3 hours under a protective atmosphere; (5) after the stirring is completed, solid-liquid separation is performed, the mixture is washed with oxygen-free deionized water for 1 to 5 times, and vacuum freeze-dried for 8 to 12 hours to obtain a dry black solid which is sulfide nanometer zero-valent iron (S0 / nZVI), sulfide nano zero-valent iron (S 0 / nZVI) is a layer of sulfur S attached to the surface of nano zero-valent iron 0 .

[0061] Example 2: (1) Nano-zero-valent iron is prepared by any one of the following methods: liquid phase reduction preparation method, ball milling method, electrolytic preparation method, and green synthesis preparation method; (2) Under a protective atmosphere (argon), the nano-zero-valent iron in step (1) is added to oxygen-free deionized water and stirred at a speed of 50 to 200 rpm; (3) Under a protective atmosphere (argon), sodium sulfide nonahydrate is added to the solution in step (2) and dissolved to obtain a sulfur-containing solution, and then stirred for 10 minutes at a stirring speed of 50 to 200 rpm; the molar ratio of sodium sulfide nonahydrate to nano-zero-valent iron is 0.24:1 to 0.06:1; (4) Under a protective atmosphere (argon), sodium sulfide heptahydrate is added to the solution in step (2) and dissolved to obtain a sulfur-containing solution, and then stirred for 10 minutes at a stirring speed of 50 to 200 rpm. The ferrous acid is fully dissolved in the solution in step (3), and the stirring speed is 50-200 rpm, wherein the molar ratio of ferrous sulfate heptahydrate to sodium sulfide nonahydrate is 1:1; (5) under a protective atmosphere (argon), the solution in step (4) is continued to be stirred to obtain black particles, and the stirring speed is 50-200 rpm, and the stirring time is 0.5-3h; (6) after the stirring is completed, solid-liquid separation is performed, and the mixture is washed with oxygen-free deionized water for 1-5 times, and vacuum freeze-dried for 8-12 hours to obtain a dry black solid, which is sulfide nano zero-valent iron (FeS@nZVI), and the sulfide nano zero-valent iron (FeS@nZVI) is a FeS shell layer formed on the surface of the nano zero-valent iron.

[0062] Example 3: (1) Under a protective atmosphere (argon), sodium sulfide nonahydrate is added to oxygen-free deionized water and stirred at a speed of 50 to 200 rpm; (2) Under a protective atmosphere (argon), ferrous sulfate heptahydrate is fully dissolved in the solution in step (1) and stirred for 10 min at a stirring speed of 50 to 200 rpm, wherein the molar ratio of ferrous sulfate heptahydrate to sodium sulfide nonahydrate is 1:1; (3) Nano-zero-valent iron is prepared by any one of the preparation methods selected from the group consisting of liquid phase reduction preparation method, ball milling method, electrolytic preparation method, and green synthesis preparation method, and the nano-zero-valent iron is added to the solution in step (2) at a stirring speed of 100 to 200 rpm. The stirring speed is 50-200 rpm and the process is carried out under a protective atmosphere (argon); the molar ratio of sodium sulfide nonahydrate to nano zero-valent iron is 0.24:1-0.06:1; (4) the solution in step (3) is further stirred to obtain black particles, the stirring speed is 50-200 rpm, the sulfidation stirring time is 1 hour, and the process is carried out under a protective atmosphere (argon); (5) after the stirring is completed, solid-liquid separation is performed, the mixture is washed with oxygen-free deionized water for 3 times, and vacuum freeze-dried for 8 hours to obtain a dry black solid, which is sulfided nano zero-valent iron (FeS / nZVI). The sulfided nano zero-valent iron (FeS / nZVI) is a layer of FeS adhered to the surface of the nano zero-valent iron.

[0063] FeSx@nZVI is prepared, for example, by the following method: (1) under a protective atmosphere (argon), sodium sulfide nonahydrate is fully dissolved in oxygen-free deionized water, the stirring speed is 600 rpm, and the experimental condition is to place the solution in a 70°C water bath for heating, and the stirring time is 2 to 4 hours; (2) under a protective atmosphere (argon), sulfur is fully stirred in the solution in step (1), the stirring speed is 400 to 600 rpm, and the experimental condition is to place the solution in a 70°C water bath for heating, and the stirring time is 2 to 4 hours, wherein the molar ratio of sodium sulfide nonahydrate to sulfur is 1:1; (3) nano zero-valent iron is prepared by any one of the preparation methods selected from liquid phase reduction preparation method, ball milling method, electrolytic preparation method, and green synthesis preparation method, and the nano zero-valent iron is added to the sulfur-containing solution in step (2) under a protective atmosphere. The solution was stirred for 10 minutes at a stirring speed of 50 to 200 rpm; (4) under a protective atmosphere, ferrous sulfate heptahydrate was fully dissolved in the solution in step (3) at a stirring speed of 50 to 200 rpm, and the molar ratio of sodium sulfide nonahydrate to nano zero-valent iron was 0.24:1 to 0.06:1; (5) under a protective atmosphere, the solution in step (4) was continued to be stirred to obtain black particles at a stirring speed of 50 to 200 rpm, and the sulfidation stirring time was 1 hour; (6) after the stirring was completed, solid-liquid separation was performed, the mixture was washed with oxygen-free deionized water for 3 times, and vacuum freeze-dried for 8 hours to obtain a dry black solid, which was sulfided nano zero-valent iron (FeSx / nZVI). The sulfided nano zero-valent iron (FeSx / nZVI) was a layer of FeSx adhered to the surface of the nano zero-valent iron.

[0064] Example 4: (1) Under a protective atmosphere (argon), take ferrous chloride (FeCl 2 ) is fully dissolved in 250 ml of oxygen-free deionized water, and the stirring speed is 50-200 rpm; (2) under a protective atmosphere (argon), sodium chloride (NaCl) is fully dissolved in the solution in step (1), and the stirring speed is 50-200 rpm. The molar ratio of ferrous chloride to sodium chloride is 1:1; (3) under a protective atmosphere (argon), commercial sulfur (S 0 comm ) is added to the solution in step (2), and stirred for 10 minutes at a stirring speed of 50 to 200 rpm. The molar ratio of ferrous chloride to sodium chloride to commercial sulfur is 2:2:1; (4) Nano-zero-valent iron is prepared by any one of liquid phase reduction preparation method, ball milling method, electrolytic preparation method, and green synthesis preparation method. Under a protective atmosphere, nano-zero-valent iron is added to the sulfur-containing solution in step (2), and stirred for 10 minutes at a stirring speed of 50 to 200 rpm; (5) The solution in step (4) is further stirred to obtain black particles. The stirring speed is 50 to 200 rpm. The sulfurization stirring time is 1 hour, and the mixture is carried out under a protective atmosphere (argon); (6) After the stirring is completed, solid-liquid separation is performed, and the mixture is washed 3 times with oxygen-free deionized water, and then freeze-dried in a vacuum for 8 hours to obtain a dry black solid as sulfide nano-zero-valent iron (S 0 comm / nZVI), sulfide nano zero-valent iron (S 0 comm / nZVI) is the sulfur element S attached to the surface of nano zero-valent iron 0 .

[0065] The preparation method of sulfide nano zero-valent iron provided by the present invention enables nano zero-valent iron to have unique surface characteristics, high adsorption capacity and strong stability, and can effectively capture ionic thallium in water, and the thallium removal efficiency is high. In addition, when sulfide nano zero-valent iron is used in the process of wastewater thallium removal treatment, no additional chemical auxiliary reagents are required, it has good environmental adaptability and can reduce secondary pollution, making the process of sulfide nano zero-valent iron used in wastewater thallium removal treatment green and environmentally friendly. When sulfide nano zero-valent iron is used in wastewater thallium removal treatment, its reaction product is, for example, non-toxic and relatively stable compounds such as ferric oxide or ferric oxide, which can be separated by magnetic separation method, and will not cause secondary pollution to the water environment, so it has good sustainability. Specific embodiments

[0067] Thallium-containing wastewater comes from surface water, groundwater and sewage, and the thallium content is 5 mg / L.

[0068] First, prepare nano zero-valent iron by any one of liquid phase reduction preparation method, ball milling method, electrolytic preparation method and green synthesis preparation method, and take 1g of nano zero-valent iron;

[0069] Secondly, under a protective gas (argon) atmosphere, 1 g of nano zero-valent iron was added to 250 mL of oxygen-free deionized water and stirred to obtain a nano zero-valent iron suspension; the stirring speed was 50 to 200 rpm, and the stirring time was 10 to 30 min;

[0070] Then, under a protective gas (argon) atmosphere, sodium sulfide nonahydrate is added to the nano zero-valent iron suspension and stirred to obtain a sulfur-containing solution; the stirring speed is 50 to 200 rpm, the stirring time is 10 to 20 minutes, and the molar ratio of sodium sulfide nonahydrate to nano zero-valent iron is 0.06:1 to 0.24:1; wherein, referring to Fig. 9 , Fig. 9 The vertical axis is the concentration of thallium in the wastewater after reaction / the concentration before reaction. Fig. 9 The different curves are the sulfide nano zero-valent iron (S) prepared under different molar ratios of sodium sulfide nonahydrate to nano zero-valent iron (0.06:1 to 0.24:1). 0 @nZVI) shows the change curve of thallium removal from wastewater (thallium content is 5 mg / L) over time (0-180 min). As time goes by, the smaller the value of thallium post-reaction concentration / pre-reaction concentration is, the better the thallium removal effect is.

[0071] Then, add ferric chloride hexahydrate into the sulfur-containing solution, and stir the ferric chloride hexahydrate and the sulfur-containing solution under a protective gas (argon) atmosphere at a stirring speed of 50 to 200 rpm for a stirring time of 0.5 to 3.0 h to obtain a sulfurized product.

[0072] Then, the sulfide product is subjected to solid-liquid separation to obtain sulfide nano zero-valent iron solid, and the sulfide nano zero-valent iron is washed with oxygen-free deionized water to obtain washed sulfide nano zero-valent iron; the washed sulfide nano zero-valent iron is freeze-dried in a vacuum atmosphere to obtain dried sulfide nano zero-valent iron; wherein the washing times are 1 to 5 times, and the freeze-drying time is 8 to 12 hours.

[0073] Finally, the prepared sulfide nano zero-valent iron was added to the untreated thallium-containing wastewater to remove thallium (without adjusting the pH value and water temperature of the thallium-containing water). The prepared sulfide nano zero-valent iron was used as a thallium removal material, and the dosage was 50-500 mg / L. The temperature was 25°C for the thallium removal test, and the reaction was carried out for 180 minutes to complete the thallium removal of the wastewater. The solid-liquid separation was performed to obtain the purified liquid after thallium removal and the thallium removal slag. The thallium content in the purified liquid after thallium removal was 0.032 mg / L, and the calculated thallium removal rate was 99.36%, indicating that the sulfide nano zero-valent iron has a high efficiency in thallium removal.

[0074] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.

[0075] In addition, it can be understood that the aforementioned embodiments are only exemplary descriptions of the present invention. Under the premise that the technical features do not conflict, the structures do not contradict, and the purpose of the present invention is not violated, the technical solutions of the various embodiments can be arbitrarily combined and used in combination.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing sulfide nano zero-valent iron, characterized in that: include: Adding nano zero-valent iron into oxygen-free deionized water for a first stirring treatment to obtain a nano zero-valent iron suspension; adding sodium sulfide nonahydrate into the nano zero-valent iron suspension for a second stirring treatment to obtain a sulfur-containing solution; adding ferric chloride hexahydrate to the sulfur-containing solution and performing a third stirring treatment to obtain a sulfurized product; The sulfided product is subjected to solid-liquid separation to obtain sulfided nanometer zero-valent iron.

2. The method for preparing sulfide nano zero-valent iron according to claim 1, characterized in that: The molar ratio of the sodium sulfide nonahydrate to the nano zero-valent iron is 0.06:1 to 0.24:1; and / or the molar ratio of the ferric chloride hexahydrate to the sodium sulfide nonahydrate is 2:

1.

3. The method for preparing sulfide nano zero-valent iron according to claim 1, characterized in that: The nano zero-valent iron is prepared by any one of a liquid phase reduction preparation method, a ball milling method, an electrolytic preparation method, and a green synthesis preparation method.

4. The method for preparing sulfide nano zero-valent iron according to claim 1, characterized in that: The first stirring process is performed under a protective gas atmosphere, the stirring speed of the first stirring process is 50 to 200 rpm, and the stirring time of the first stirring process is 10 to 30 min; And / or, the second stirring treatment is performed under a protective gas atmosphere, the stirring speed of the second stirring treatment is 50 to 200 rpm, and the stirring time of the second stirring treatment is 10 to 20 min; And / or, the third stirring treatment is performed under a protective gas atmosphere, the stirring speed of the third stirring treatment is 50 to 200 rpm, and the stirring time of the third stirring treatment is 0.5 to 3.0 h.

5. The method for preparing sulfide nano zero-valent iron according to claim 1, characterized in that: After the sulfidation product is subjected to solid-liquid separation to obtain sulfided nano zero-valent iron, the method further comprises: Washing the sulfide nanometer zero-valent iron with oxygen-free deionized water to obtain washed sulfide nanometer zero-valent iron; the washing times are 1 to 5 times; In a vacuum atmosphere, the washed sulfide nano zero-valent iron is freeze-dried to obtain dried sulfide nano zero-valent iron; the freeze-drying time is 8 to 12 hours.

6. A sulfide nano zero-valent iron, characterized in that: The invention is prepared by the preparation method of sulfide nano zero-valent iron according to any one of claims 1 to 5.

7. The sulfide nano zero-valent iron according to claim 6, characterized in that: The chemical formula of the sulfide nano zero-valent iron is S 0 @nZVI.

8. A method for removing thallium from wastewater, characterized in that: The thallium-containing wastewater to be treated is treated with the sulfide nano-zero-valent iron as described in claim 6 or 7 to remove thallium.

9. The method for removing thallium from wastewater according to claim 8, characterized in that: include: Adding the sulfide nanometer zero-valent iron to the thallium-containing wastewater to be treated to remove thallium, thereby obtaining a reaction product; The pH value of the thallium-containing wastewater to be treated ranges from 3 to 11; The product after the reaction is subjected to solid-liquid separation to obtain the liquid after thallium removal and thallium removal slag.

10. The method for removing thallium from wastewater according to claim 8, characterized in that: Calculated by the volume of the thallium-containing wastewater, the thallium concentration of the thallium-containing wastewater is 5 mg / L, and the dosage of the sulfide nano zero-valent iron is 50-500 mg / L.

Citation Information

Cited By

  • Composite material for adsorbing heavy metal thallium and preparation method thereof

    CN121623736A